The Influence of Health Education on Pregnant Women's Knowledge of Gestational Diabetes Mellitus - Elizar Elizar; Irnawati Irnawati; Gustiana Gustiana; Nurmila Nurmila; Rosyita Rosyita; Hendrika Wijaya Kartini Putri (Care : Jurnal Ilmiah Ilmu Kesehatan, 2026)
Gestational diabetes mellitus is a common complication during pregnancy that can increase maternal and fetal morbidity as well as long-term health risks. Therefore, improving pregnant women's knowledge is essential for early detection, prevention, and appropriate management. The purpose of this research is to examine how health education affects pregnant women's comprehension of gestational diabetes mellitus. This study employed a quasi-experimental design with a one-group pre-post approach. A total of 61 pregnant women attending antenatal care at the independent midwifery practice of Salabiah in Lhokseumawe City were selected through purposive sampling. Participants were pregnant women with a Maternal and Child Health handbook, without mental disorders, previous pregnancy complications, or gestational diabetes mellitus. Knowledge was measured using a structured questionnaire administered before and after the educational intervention, which was delivered through a lecture method. The Wilcoxon Signed-Rank Test revealed a significant difference in knowledge scores pre- and post-intervention (p 0.05), demonstrating a notable increase in the average post test score. These results suggest that health education successfully enhances the knowledge of pregnant women regarding gestational diabetes mellitus. Integrating structured and comprehensible educational programs into routine antenatal care is recommended to enhance maternal awareness and promote better pregnancy outcomes.